Cranioschisis And Meningocele In A Buffalo Calf: A Case Report - Kumar, V. Prasanna; Gowda, C.T. Chandre; Kumar, V. Pradeep (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Genetic and non-genetic defects associated with recessive genes are primarily responsible for fetal developmental abnormalities (Roberts, 1986). Cranioschisis refers to failure of fusion of cranial bones, which results in herniation of meninges. Meningocele is the herniation of meninges filled with cerebrospinal fluid but does not contain neural tissue, whereas meningoencephalocele is the herniation of meninges along with brain tissue through the defect in skull (Hoogmoed et al., 1999). Determination of factors leading to development of cranioschisis and meningocoele is difficult since they are numerous such as malnutrition, exposure to diseases, use of medicines and growth conditions (Yaman et al., 2013). A little information is known about cranioschisis and meningocele in buffalo calves and only few cases related to these defects are reported till date (Ayyappan et al., 1996; Manda et al., 2007 and Pandey et al., 2012). In the present study, an unusual case of buffalo calf with cranioschisis and meningocele is discussed.